Comparison of Pain and Anxiety Scales in The First and Second Cataract Surgeries in Patient with Bilateral Cataract: Oral Presentation - Observational Study - Resident - SARAH EISYA PUTRI; Ahmad Ashraf Amalius; Andi Akhmad Faisal; M. Irfan Kamaruddin (Majalah Oftalmologi Indonesia, 2023)
Abstract : Introduction & ObjectivesPain and anxiety in cataract surgery can be investigated as subjective experiences and satisfaction. This study was to evaluate and compare pain and anxiety scale reported by patients with bilateral cataract in the first and second surgery. Methods : This prospective study was based on patients in Jakarta Eye Centre Orbita Makassar between August-October 2022. Consecutive patients undergoing bilateral cataract surgery with the first and second surgery separated by minimum of two weeks with phacoemulsification method and used topical anaesthesia, by three surgeons. Patients with traumatic cataract, secondary cataract, and other ocular abnormality, also patients with intraoperative complications were excluded. Patients completed questionnaires of Numerical Rating Scale to evaluate pain and Amsterdam Preoperative Anxiety and Information Scale (APAIS) to evaluate anxiety divided into no, mild, moderate, severe, and very severe anxiety. Results : A total of 42 patients with an average of 64,5 years old were included. There were 2 (4.7%) patients reported more pain in the first surgery, 30 (71%) patients reported more pain in the second surgery, and 10 (23%) patients reported same pain between the first and second surgeries (p=0,000). Most patients reported mild anxiety in the first surgery and no anxiety in second surgery. Conclusion : Patients with bilateral cataracts reported more pain on the second surgery than the first surgery. The anxiety was reported more severe before and during the first surgery than the second surgery. This report can be used in giving informed concern and in the management of bilateral cataract surgeries consecutively.